Faktor FAKTOR PENGARUH TERHADAP RETURN SAHAM DI PERUSAHAAN PROPERTI, REAL ESTATE, DAN KONSTRUKSI BANGUNAN DI BURSA EFEK INDONESIA - ADITYA NANDA KRISNA; Hendra Hendra (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this research is to analyze whether the factors contained in this research affect on stock returns in property, real estate, and building construction companies that listed on Indonesia Stock Exchange in 2013-2020. The factors studied are the current ratio, debt to equity ratio, return on equity, asset turnover, and dividend payout ratio. Purposive sampling is used as the sample collection technique and there are 6 companies that fulfilled the criteria and analyzed using panel data regression and the common effect model was chosen as the best model for this research. The results of this research are that there is no effect of the current ratio, debt to equity ratio, return on equity, total asset turnover, and dividend payout ratio on stock returns.